Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1051/0004-6361:20054604
|View full text |Cite
|
Sign up to set email alerts
|

Observations of simultaneous coronal loop shrinkage and expansion during the decay phase of a solar flare

Abstract: We report what we believe are the first direct and unambiguous observations of simultaneous coronal magnetic flux loop shrinkage and expansion during the decay phase of a solar flare. The retracting and expanding loops were observed nearly face-on (i.e., with the loop major axis approximately orthogonal to the line of sight) in emission in imaging data from the Yohkoh Soft X-ray Telescope (SXT). The retracting loop is observed to shrink with a speed of 118 ± 66 km s −1 . The faint outward moving loop-like feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The author reported that HXR sources (14 − 23 keV) were observed for about 50 minutes after flare maximum. The HXR source existing more than 1 hour after flare maximum was also reported by Khan et al (2006). In all these cases the HXR emission was observed close to and above the SXR emission source.…”
supporting
confidence: 74%
“…The author reported that HXR sources (14 − 23 keV) were observed for about 50 minutes after flare maximum. The HXR source existing more than 1 hour after flare maximum was also reported by Khan et al (2006). In all these cases the HXR emission was observed close to and above the SXR emission source.…”
supporting
confidence: 74%
“…Observations of inward moving waves do not necessarily support the idea of implosion. Inward moving waves, together with outward moving waves, may be produced by the reconnection event (Khan et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This flare has a variety of interesting phenomena, some of which have been examined and reported elsewhere (Khan et al 2000;Klassen et al 2001;Hudson et al 2003;Khan et al 2006). In particular, Khan et al (2006) found simultaneous retracting and expanding soft X-ray emitting coronal loops above the main flaring arcade during the decay phase of the flare. The supra-arcade downflows appeared shortly after these moving loops.…”
Section: Downflows Starting During the Flare Decay Phasementioning
confidence: 91%
“…Recently, Khan et al (2006) reported observations of simultaneous retracting and expanding distinct coronal loops observed in emission in soft X-rays during a solar flare. For the particular event they examined, there were also supra-arcade downflows and these were clearly observed to start during the decay phase of the flare.…”
Section: Introductionmentioning
confidence: 99%